A five-year retrospective analysis of clinical, pathological and treatment aspects on stomach cancer from a regional cancer centre in north east India - Mahawar, Rahul; S. Devi, Yumkhaibam; D. Devi, Ningthoujam; Panmei, Ruby; Babu B., Mohan; Malsawmtluanga, Benjamin (International Journal of Research in Medical Sciences, 2023)
Background: Stomach cancer is the fifth most common cancer in the world, which generally presents in advanced stage and have poor prognosis. Methods: Retrospective study including 101 cases was done at the Regional Cancer Centre in North East India from January, 2018 to December, 2022 on the clinical, pathological and treatment aspects of stomach cancer. Results: Median age of diagnosis was 59 years, with high male: female ratio. Most common risk factor was tobacco smoking and chewing. Most common symptom was pain abdomen followed by nausea or vomiting. Antrum was the most common tumor location, and gastric outlet obstruction was present in 10.9% patients. Histologically, all patients had adenocarcinoma, with metastasis found in 47 patients. Out of the 101 patients enrolled in the study, 50 patients were treated with curative intent and the remaining 51 patients were treated with palliative intent. Patients were treated with surgery, preoperative/ adjuvant/ palliative chemotherapy and/or curative/ palliative radiotherapy. Conclusions: This study showed tobacco use as an important risk factor for stomach cancer. Majority of our patients were diagnosed at an advanced stage, thus having poor prognosis. Hence, avoidance of risk factors, early detection of signs and symptoms, and aggressive treatment with surgery, chemotherapy, and/ or radiotherapy is required for management of stomach cancer.